Impact Of Working Mother To Children’s Health In Indonesia - Nadia Cahya Dwinanda; Wiksadana wiksadana; Estro Dariatno Sihaloho; Herlina Silvani Purba Tambak (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2021)
There are still many challenges facing the field of child health in Indonesia. Children's health is crucial due to its role in Indonesia’s future economic development and growth. The objective of this research is to determine the consequence of a mother’s work status on children's health. Other factors such as the effect of the location of residence (urban and rural) and the level of mother's education are also evaluated on children's health. This study was conducted using data obtained from IFLS 5 (Indonesia Family Life Survey 5) in 2014 with a sample size of 8,907 individuals. This study utilizes the Binary Logit regression method using STATA 14. The results indicated that the status of a mother’s work has a significant and negative effect on the level of children's health, while the mother's education level and location of residence (urban) have a significant and positive effect on the level of children's health. This research implies the promotion of education for future improvements in child health. Keywords: Child Health; Mother's Education Status; Mother's Work Status; Place of Residence